The Church Ensemble of Una and the Actual Research Problems of the Wooden Architecture of the White Sea Region - Khodakovsky, Evgeny V. (Actual Problems of Theory and History of Art, 2017)
The article is devoted to one of the least studied monuments of wooden architecture of the Russian North — the Church of St. Clement in the village of Una, not far from the Summer coast of the White Sea. The church was lost in fire in the late 19th century, and the evidence on its history is extremely scarce. As a result of archival research the author sets the exact date of the construction and consecration of the Church of St. Clement in Una (1771–1783), the year of its destruction in the fire (1899). The article reveals the whole history of Una ensemble, which consisted of Trinity Church (1769–1771, rebuilt in 1848 and 1863) and the bell tower (1787, 1902). In the light of the newly discovered dates of Una churches, built in 1760–1780s, these monuments are considered not only in the typological series of tent-roofed churches of the Dvina Bay and the Summer coast of the White Sea (Nenoksa, Patrakeevka, Konetsdvor’e), but also in the broader context of the ensemble construction of the second half of the 18th century in the Onega river basin and in the White Sea (Liadiny, Turchasovo, Podporozhye, Piyala).
Keywords: Russian wooden architecture; Russian North; the White Sea; archival and source studies; ensemble building; Vladimir Suslov